ASYMMETRIC EFFECTS OF EXCHANGE RATE VOLATILITY ON TRADE AND INVESTMENT: A NONLINEAR APPROACH - Amraoui, Karima; Harrak, Soukaina Alami; El-Khodary, Mohammed (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Exchange rate movements play a central role in shaping external competitiveness, yet their effects are rarely symmetric and are often underestimated in studies that rely on linear models. This article examines how real effective exchange rate (REER) appreciations and depreciations influence the external sector in Morocco, focusing on foreign direct investment (FDI), exports, and imports over 1988–2023. Annual data from the World Development Indicators are analyzed using a Nonlinear Autoregressive Distributed Lag (NARDL) model, which decomposes REER into appreciation and depreciation components. Cointegration is assessed through bounds testing, while Wald statistics evaluate the presence of short- and long-run asymmetries. The results show that appreciations have sharper and more immediate impacts than depreciations across all channels. In the short run, appreciation reduces FDI and exports while boosting imports, though some of these effects are later corrected. Depreciation produces weaker and delayed responses, reflecting the economy’s dependence on imported inputs for exports and essential goods. Over the long run, imports display significant asymmetry, exports respond largely symmetrically, and FDI reveals a delayed rebound after appreciation, highlighting the credibility effect of currency stability. The novelty of this study lies in combining a long horizon with a nonlinear approach rarely applied to Morocco, uncovering dynamics overlooked by linear models, most notably the rebound of FDI and exports following appreciation and the structural rigidity of imports. These findings suggest that sustaining competitiveness requires more than exchange rate management; export diversification, financial deepening, and industrial upgrading are crucial to mitigating appreciation shocks and enhancing resilience.